Pengaruh Sistem Pengendalian Intern, Otonomi Daerah Dan Kompetensi Perangkat Desa Terhadap Pengelolaan Keuangan Desa Menurut Undang-Undang No. 20 Tahun 2018 - Amilliyah, Winda Ayu; Biduri, Sarwend (Wadah Inovasi Indonesia, 2023)
This study examines the influence of the Internal Control System, Regional Autonomy, and Village Apparatus Competency on Village Financial Management in accordance with Law no. 20 of 2018. A quantitative approach was used with a research sample of 16 villages in Porong District, Sidoarjo. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the analysis show that the Internal Control System, Regional Autonomy, and Competence have a significant effect on Village Financial Management (sig < 0.05). Taken together, the three variables are able to explain 62.9% of the variation in Village Financial Management. This research provides an understanding of the factors that influence village financial management and can be a reference for village officials in improving village financial performance.